Uma abordagem baseada em blockchain para a governança da cadeia de suprimentos - Gomes, Alan Nascimento (2023)
A supply chain can be defined as an interconnected network of individuals, companies, resources, processes and technologies involved in the manufacture and sale of a product or service. Agreements are constantly made in these networks with the aim of the parties exchanging assets. These agreements can be made through strict contracts or even simple relationships of trust that the parties have between themselves. Due to the high growth of the supply chain and the intensification of the complexity of relationships in this network, trust in negotiations has become increasingly undermined, especially in those in which this characteristic is the main guarantee of agreements. The mechanisms adopted to ensure a good exchange between those involved can be achieved through the implementation of governance in relationships. In this context, it defines how interested parties will act in the construction of their interactions, thus generating relationships with desirable characteristics, such as trust. In this way, current technologies can enable the application of governance in supply chains. Blockchain can act as a tool to mitigate the lack of trust in supply chain relationships, due to characteristics such as integrity, immutability and decentralization of information. Under this bias, this work aims to propose a solution to enable trust in relational governance between members of the supply chain using blockchain technology. With the aim of evaluating the state of the art on the topic of governance in the blockchain-based supply chain, a mapping was carried out in the literature with the purpose of searching for related works on the terms: governance, supply chain and blockchain. The proposed approach is based on a permissioned blockchain, the Hyperledger Fabric framework. Metrics were proposed to evaluate supply chain relationships, which were: reliability, engagement and transparency. The results of this research show that metrics are relevant for evaluating relationships in the supply chain and blockchain technology is a tool that can improve relational governance in this area.